Cytotoxic, analgesic and anti-inflammatory activity of colchicine and its C-10 sulfur containing derivatives - Kurek, Joanna (Sci Rep, 2021)
10-Alkylthiocolchicines have been obtained and characterized by spectroscopic methods and their biological activities as: cytotoxic, anti-inflammatory and analgesic activities have been tested. Cytotoxic activity against SKOV-3 ovarian cell line for 10-alkylthiocolchicine analogues was reported and tested compounds showed to be more active than commonly used doxorubicin. Some of tested C-10 alkylthiolated colchicines have been found to exhibit cytotoxicity at levels comparable to that of the natural product—colchicine. 10-Methylthiocolchicine has IC(50) = 8 nM and 10-ethylthiocolchicine has IC(50) = 47 nM in comparison to colchicine IC(50) = 37 nM. Moreover for 10-alkylthioderivatives apoptosis test, cyclin B1 and cell cycle tests were performed. 10-n-Butylthiocolchicine was tested for anti-inflammatory and analgesic activities it showed to produce analgesic rather than anti-inflammatory effect.